A quantification of the short-term reliability of HDPE geomembrane seaming methods. Issue 4 (7th August 2022) - Gilson-Beck, A.; Giroud, J. P.
Abstract : This study provides a preliminary approximate quantification of the difference in seam reliability between fusion seams and extrusion seams of high-density polyethylene (HDPE) geomembranes based on leaks that exist at the end of installation. The two different seaming methods as well as seam testing methods are discussed. The reliability of the two seaming methods is compared using the number of leaks associated with extrusion seams versus fusion seams, which were found using electrical leak location surveys performed on a sampling of large geomembrane-lined facilities.